2013
DOI: 10.1039/c2ta00450j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical design of highly active SrTiO3-based photocatalysts by a codoping scheme towards solar energy utilization for hydrogen production

Abstract: SrTiO 3 is a promising photocatalyst for the production of hydrogen from water splitting under solar light. Cr doping is an effective treatment for adjusting its absorption edge to the visible-light range, although the performance of Cr-doped SrTiO 3 is strongly affected by the oxidation number of the Cr ions. In this study, we theoretically predict that elevating the Fermi level, i.e., n-type carrier doping in SrTiO 3 , can stabilize the desirable oxidation number of chromium (Cr 3+), contributing to a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 37 publications
4
87
0
Order By: Relevance
“…Such a deviation of photocatalytic activity from light absorption implies that other factors might dominate the catalytic performance at high Cr content. According to XPS analysis above, this is likely due to the enrichment of Cr at the surface in sample ZnGa 0.5 Cr 1.5 O 4 as Cr is treated as an active element in many photocatalytic systems [22,24,25]. A plot of hydrogen evolution rate with the amount of Cr at the surface according to XPS clearly shows the positive effect of Cr (Fig.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 88%
See 1 more Smart Citation
“…Such a deviation of photocatalytic activity from light absorption implies that other factors might dominate the catalytic performance at high Cr content. According to XPS analysis above, this is likely due to the enrichment of Cr at the surface in sample ZnGa 0.5 Cr 1.5 O 4 as Cr is treated as an active element in many photocatalytic systems [22,24,25]. A plot of hydrogen evolution rate with the amount of Cr at the surface according to XPS clearly shows the positive effect of Cr (Fig.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 88%
“…It is known that the physical and chemical properties of host materials are significantly altered by the amount of dopants and optimized doping content is often seen for the photocatalytic performance of host semiconductors [19][20][21][22]. Since chromium has generally been served as a low cost dopant for the modification of various wide band gap semiconductors [20,[22][23][24][25][26], the comparable ionic radius between Cr 3 þ (0.615 Å) and Ga 3 þ (0.62 Å) strongly implies the possible formation of wide range solid solution of chromium in ZnGa 2 O 4 [27,28]. More importantly, ZnCr 2 O 4 has been reported to exhibit high photocatalytic hydrogen production [17], it is therefore very interesting to investigate the photocatalytic activity of Cr doped ZnGa 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium-based perovskite oxides such as ATiO 3 (A = Ba and Sr) have been investigated as a class of promising photocatalysts [18]. Attempts were made to improve the photocatalytic activity of BaTiO 3 and SrTiO 3 through doping them with metals or non-metals or creating heterojunctions [19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works have addressed the photo-catalytic activity of SrTiO 3 alone, with other transition metals as well as doped with other ions [5][6][7][8][9][10][11]. Results differ strongly from one study to the other due to difference in crystallinity, metal dispersion, effect of dopant and reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent computational study (using the hybrid DFT method) of doping SrTiO 3 with metal cations coupled with experimental study showed that co-doping Cr and La ions had considerable enhancement effect on hydrogen production of water/methanol solution [11]. The reason invoked is that doping with La ions raised the Fermi level of Cr ions and stabilizes its oxidation state of Cr 3?…”
Section: Introductionmentioning
confidence: 99%